(untitled) (Iranian Journal of Kidney Diseases, 2013)
Necrotizing fasciitis is a rare complication of nephrotic syndrome in children, with a high mortality rate. We report a case with successful outcome with judicious intravenous antibiotics and skin grafting of the bilateral lower thighs.